Toward a Phylogenetic-based Generic Classification of Neotropical Lecythidaceae—II. Status of Allantoma, Cariniana, Couratari, Couroupita, Grias and Gustavia - Mori, Scott A.; Smith, Nathan P.; Huang, Ya-Yi; Prance, Ghillean T.; Kelly, Lawrence M.; Matos, Carol Carollo (Phytotaxa, 2015)
The morphological features of all clades of neotropical Lecythidaceae subfam. Lecythidoideae (Brazil nut family) with actinomorphic androecia (Allantoma, Grias, Gustavia) as well as three clades with zygomorphic androecia (Cariniana, Couroupita, and Couratari) are described. These clades are those that were recovered by a phylogeny based on molecular data, and all, except Allantoma and Cariniana, have been recognized as genera without changes for over a hundred years. The latter two genera have recently been circumscribed such that they now also represent monophyletic clades; thus, the authors conclude that the clades discussed in this paper represent well-defined genera based on both morphological and molecular data. Morphological descriptions of these six clades of the non-Bertholletia clade are included and a key to the 16 clades of New World Lecythidaceae is presented.